Long-term mortality of adult patients with carbon monoxide poisoning presenting to the emergency department in Korea: a population-based cohort study - Lee, Sang Hwan; Ryu, Soo Rack; Yoo, Kyung Hun; Lee, Juncheol; Cho, Yongil; Lim, Tae Ho; Kang, Hyunggoo; Oh, Jaehoon; Ko, Byuk Sung (Acute and critical care, 2024)
Background: Carbon monoxide (CO) poisoning can lead to significant morbidity and mortality. However, relatively few studies have investigated its long-term mortality impact. This nationwide population-based cohort study examined the association between CO poisoning and long-term mortality.Methods: This retrospective study utilized data from the National Health Insurance Service database in South Korea. We compared the patients with CO poisoning to those without CO poisoning. Inverse probability treatment weights were applied to both groups to control for potential confounding factors. Subsequently, mortality was assessed using the incidence rate and Cox proportional hazard ratios.Results: This study included 23,387 patients with CO poisoning and 359,851 without it. Over a median follow-up period of 7.6 years after CO poisoning diagnosis, the mortality risk was 2.6 times higher in patients with CO poisoning compared to that in the control group. In a long-term follow-up of patients surviving beyond 30 days, mortality remained 2.18 times higher. Additionally, a higher mortality risk was observed in the relatively younger age group (18–39 years) and the group with fewer underlying diseases, as indicated by a Charlson Comorbidity Index score of 0.Conclusions: CO poisoning is associated with an elevated long-term mortality rate particularly in a relatively young and healthy population.